Investigation on Combustion Characteristics and Thermal Efficiency of Cylindrical Biomass Stove - Tompat, Pornpitak; Pianthong, Kulachate; Dincherdchu, Jing (Srinakharinwirot University Engineering Journal, 2023)
This research aims to investigate combustion characteristics and thermal efficiency of the cylindrical biomass stove by the water boiling test method. This is to find out the optimum condition for further application. Major parameters, which are the compression pressure and the moisture content of the biomass, are varied on the preparation of the stove. The biomass in the experiment is sawdust and is compressed in a cylindrical stove at pressure of 40 bar, 80 bar, and 120 bar, while the moisture content of the sawdust are 10%, 15%, 20% and 25%. From the investigation, it is shown that the stove with compression pressures of 40 bar, 80 bar and 120 bar can operate continuously for 4 hours, 6 hours and 7 hours, respectively. The 15% moisture and 40 bar compression gives the highest flame temperature of 703 ๐C. While the 15% sawdust moisture of all compression pressures gives the highest thermal efficiency at 16.24%, 14.38 and 20.26% at the 2nd hour of the operation of the stove.